Primary intratesticular rhabdomyosarcoma: a rare aggressive childhood neoplasm - Kumar, Rajnish; Sethi, Bhawna; Maletha, Madhukar (International Journal of Research in Medical Sciences, 2020)
Testicular tumors are relatively uncommon in children. The tumors of germ cell origin are still frequently encountered. The pure embryonal rhabdomyosarcomas of testis, not associated with sarcomatous component of the germ cell tumor, is a very rare entity. It is a highly aggressive tumor of childhood and young adolescents. In testes, it arises commonly from paratesticular tissue; primary intratesticular being extremely rare. To the best of authors knowledge, only fifteen cases of primary pure intratesticular tumor have been reported in the literature so far. We report a case of eight-year-old child who presented with a progressive painless right testicular enlargement over two months. Ultrasonography showed a heterogenous intratesticular mass. High orchidectomy was performed. Histopathological examination of the specimen assisted with immunohistochemistry revealed embryonal rhabdomyosarcoma.